Análisis de la inversión pública del Ecuador, destinada al sector de la salud de la ciudad de Machala. periodo 2018 - 2022. - Cardenas Cordero, Britthani Michelle; Palma Chango, Yustin Joel (Machala : Universidad Técnica de Machala, 2024)
The main objective of the project is to identify the variation in the budget allocated to the health sector in the city of Machala, province of El Oro, during the period between 2018 and 2022. To achieve this objective, specific objectives are proposed that include describing the theoretical foundations related to public investment and public health systems. The analysis will focus on understanding how public investment influences the efficiency and effectiveness of health services, as well as the financial sustainability of the system. This study will allow us to evaluate budget fluctuations and their impact on the provision of health services in the community of Machala. The implementation of budget stability mechanisms in the Machala health sector seeks to address the challenges of budget fluctuations, guaranteeing a stable allocation of resources. This will lead to greater effectiveness, efficiency and sustainability of the health system. In the short term, financial stability and agile response to emergencies are expected. In the medium term, an optimization of administrative processes and greater efficiency in the implementation of health programs is anticipated. In the long term, a sustained improvement in the quality of services and strengthened collaboration between the public and private sectors is expected.
El proyecto tiene como objetivo principal identificar la variación del presupuesto destinado al sector salud en la ciudad de Machala, provincia de El Oro, durante el período comprendido entre 2018 y 2022. Para lograr este objetivo, se plantean objetivos específicos que incluyen describir los fundamentos teóricos relacionados con la inversión pública y los sistemas de salud pública. El análisis se centrará en comprender cómo la inversión pública influye en la eficiencia y efectividad de los servicios de salud, así como en la sostenibilidad financiera del sistema. Este estudio permitirá evaluar las fluctuaciones presupuestarias y su impacto en la prestación de servicios de salud en la comunidad de Machala. La implementación de mecanismos de estabilidad presupuestaria en el sector de salud de Machala busca abordar los desafíos de fluctuaciones presupuestarias, garantizando una asignación estable de recursos. Esto conducirá a una mayor efectividad, eficiencia y sostenibilidad del sistema de salud. A corto plazo, se espera estabilidad financiera y respuesta ágil a emergencias. En el mediano plazo, se anticipa una optimización de procesos administrativos y mayor eficiencia en la implementación de programas de salud. A largo plazo, se prevé una mejora sostenida en la calidad de los servicios y una colaboración fortalecida entre los sectores público y privado.
Keywords: ESTABILIDAD PRESUPUESTARIA; SECTOR SALUD; EFECTIVIDAD; EFICIENCIA